2008
DOI: 10.1158/1055-9965.epi-07-0733
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation of P16, MGMT, and hMLH1 Genes in Combination with MTHFR C677T Genetic Polymorphism in Esophageal Squamous Cell Carcinoma

Abstract: To explore the role of aberrant hypermethylation of cancer-related genes, such as P16, MGMT, and hMLH1, in the esophageal squamous cell carcinoma (ESCC) as well as its relation to dietary folate intake and MTHFR C677T polymorphism, we conducted a molecular epidemiologic study in China. One hundred and twentyfive histologically confirmed ESCC patients having undergone surgery in the Yangzhong People's Hospital between January 2005 and March 2006 were recruited. The aberrant CpG island hypermethylation of P16, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 45 publications
8
70
1
2
Order By: Relevance
“…The main reason might be the activity of folate metabolic enzyme which participates into the methylation process of DNA. Previous studies reported that individuals carrying variant genotypes CT or TT had a higher risk of methylation of MGMT in cancer tissues (Wang et al, 2008;Chen et al, 2012). Our results are in line with previous study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The main reason might be the activity of folate metabolic enzyme which participates into the methylation process of DNA. Previous studies reported that individuals carrying variant genotypes CT or TT had a higher risk of methylation of MGMT in cancer tissues (Wang et al, 2008;Chen et al, 2012). Our results are in line with previous study.…”
Section: Discussionsupporting
confidence: 93%
“…Published data indicated that the DNA methylation primarily influences the cytosine of symmetrical dinucleotide CpG in human (Issa et al, 2004) and the subsequent pattern of DNA methylation is transmitted through mitosis and maintained after DNA replication (Gius et al, 2005), and thereby aberrant CpG island methylation could promote the carcinogenesis. It has been previously reported that P16, COX2, MGMT, hMSH2 and hMLH1 gene could be more frequently found in cancer tissues than in remote normal-appearing tissues, and hypermethylation could not be found in normal tissues (Wang et al, 2008;Chen et al, 2012;Gao et al, 2013). The present study indicated that individuals with methylation of P16 and MGMT was significantly higher in the cancer tissues, which proved DNA methylation may play a role in the development of gastric cancer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Total DNA was extracted from the buffy coat layer using a TIANamp blood DNA kit (Tiangen Biotech; Beijing, China) and centrifuged for 3 min at 13,400 g (12,000 rpm). The methylation status of MGMT and hMLH1 was determined by the methylation-specific polymerase chain reaction (PCR) method after sodium bisulfate modification of DNA (Wang et al, 2008). The pairs of primers used were designed with the Assay Design 3.1 software (Sequenom; San Diego, CA, USA; Table 1).…”
Section: Dna Extraction and Quantificationmentioning
confidence: 99%
“…Siraj et al (33) demonstrated that there was no significant association between MTHFR variant genotypes and methylation of O 6 -MGMT in diffuse large B cell lymphoma. In contrast, Wang et al (34) reported that individuals carrying the CT or TT genotype had a higher frequency of O 6 -MGMT gene hypermethylation in esophageal squamous cell carcinoma tissues. These inconclusive results suggest that there are multiple other factors modulating methylation in addition to the MTHFR C677T polymorphism.…”
Section: No Controls (%) or (95% Ci) P-value (N=247) (N=100) -------mentioning
confidence: 88%